In vivo restoration of dystrophin expression in mdx mice using intra-muscular and intra-arterial injections of hydrogel microsphere carriers of exon skipping antisense oligonucleotides - Shani Attias Cohen; Orit Bar-Am; Claudia Fuoco; Galit Saar; Cesare Gargioli; Dror Seliktar (Cell Death and Disease, 2022)
Abstract Duchenne muscular dystrophy (DMD) is a genetic disease caused by a mutation in the X-linked Dytrophin gene preventing the expression of the functional protein. Exon skipping therapy using antisense oligonucleotides (AONs) is a promising therapeutic strategy for DMD. While benefits of AON therapy have been demonstrated, some challenges remain before this strategy can be applied more comprehensively to DMD patients. These include instability of AONs due to low nuclease resistance and poor tissue uptake. Delivery systems have been examined to improve the availability and stability of oligonucleotide drugs, including polymeric carriers. Previously, we showed the potential of a hydrogel-based polymeric carrier in the form of injectable PEG-fibrinogen (PF) microspheres for delivery of chemically modified 2′-O-methyl phosphorothioate (2OMePs) AONs. The PF microspheres proved to be cytocompatible and provided sustained release of the AONs for several weeks, causing increased cellular uptake in mdx dystrophic mouse cells. Here, we further investigated this delivery strategy by examining in vivo efficacy of this approach. The 2OMePS/PEI polyplexes loaded in PF microspheres were delivered by intramuscular (IM) or intra-femoral (IF) injections. We examined the carrier biodegradation profiles, AON uptake efficiency, dystrophin restoration, and muscle histopathology. Both administration routes enhanced dystrophin restoration and improved the histopathology of the mdx mice muscles. The IF administration of the microspheres improved the efficacy of the 2OMePS AONs over the IM administration. This was demonstrated by a higher exon skipping percentage and a smaller percentage of centered nucleus fibers (CNF) found in H&E-stained muscles. The restoration of dystrophin expression found for both IM and IF treatments revealed a reduced dystrophic phenotype of the treated muscles. The study concludes that injectable PF microspheres can be used as a carrier system to improve the overall therapeutic outcomes of exon skipping-based therapy for treating DMD.